Prevalence and characteristics of malnutrition among community-dwelling older adults in Israel. (December 2018) - Sharman Moser, Sarah; Doyev, Ronit; Cohen, Billy; Kurz, Reuma; Sulo, Suela; Shalev, Varda; Chodick, Gabriel
Summary: Background & aims: Limited data are available on the characteristics of older adults (age ≥ 65) diagnosed with malnutrition in the community in Israel. This retrospective cohort study describes the prevalence and characteristics of malnutrition among a representative cohort of Israeli community-dwelling older adults. To better understand the characteristics of oral nutritional supplement (ONS) users with malnutrition, we also compared this group to non-ONS users with malnutrition. Methods: Older adults enrolled in a large not-for-profit healthcare organization in Israel were defined as malnourished according to a diagnosis of malnutrition and/or body mass index (BMI) ≤ 20 kg/m 2 . Index date was defined by the earliest indication of malnutrition. ONS purchases in the year following index date were used to classify patients into ONS and non-ONS users. Results: The malnutrition prevalence rate was 3.4%. ONS users comprised 19.9% (1881/9445) of the malnourished patients. The mean age of ONS users was higher than that of non-ONS users (80.5 vs. 75.4 years, P ≤ 0.001), and women were predominant in both groups (59.2% ONS users vs. 61.8% non-ONS users, P = 0.04). ONS users (vs. non-ONS users) were significantly (P < 0.05) more likely to have co-morbidities such as cardiovascular disease (49.5% vs. 35.1%), diabetes mellitus (26.5% vs. 20.9%), hypertension (72.2% vs. 57.4%), cancer (32.0% vs. 20.7%), and dementia (24.8% vs. 9.8%). Mean baseline BMI (up to a year before index date) was similar in ONS users (20.74 kg/m 2 ) and non-ONS users (20.26 kg/m 2 ). ONS users had higher health services utilization, including visits to primary care physicians and dietitians, and hospitalizations (P-values < 0.05). Conclusions: Malnutrition is prevalent among 3.4% of community-dwelling older Israeli adults. However, older adults are not screened and treated for malnutrition systematically. Improved guidance from healthcare professionals, including earlier nutrition screening and assessment, may lead to improved health outcomes and reduced healthcare services utilization.